Severe Gastrointestinal Hemorrhage due to Monkeypox Virus-Associated Proctocolitis - Sobaan Taj; Chris Austin; Azhar Hussain; Maryam Salma Babar; Harshavardhan Sanekommu; Steven Imburgio; Anmol Johal; Alejandro CruzPonce; Apurva Vedire; Edward Liu (Case Reports in Gastrointestinal Medicine)
Monkeypox is primarily a painful cutaneous disease with occasional systemic manifestations. Monkeypox is transmitted predominantly through close physical contact and occasionally sexual contact. The first case was reported in the United States on May 17, 2022, in a recent monkeypox worldwide outbreak. We present a case of severe gastrointestinal bleeding as an atypical manifestation of monkeypox infection in a 40-year-old male with HIV. In our case, monkeypox-induced proctocolitis progressed to severe rectal bleeding requiring one unit of packed red blood cells transfusion despite one week of tecovirimat (TPOXX) therapy. So, patients should be educated about the possibility of unusual complications of monkeypox infection, i.e., bleeding in immunocompromised hosts.